1992
DOI: 10.1128/mcb.12.8.3490
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the activation of heat shock factor in vivo and in vitro by flavonoids.

Abstract: Transcriptional activation of human heat shock protein (HSP) genes by heat shock or other stresses is regulated by the activation of a heat shock factor (HSF). Activated HSF posttranslationally acquires DNA-binding ability. We previously reported that quercetin and some other flavonoids inhibited the induction of HSPs in HeLa and COLO 320DM cells, derived from a human colon cancer, at the level of mRNA accumulation. In this study, we examined the effects of quercetin on the induction of HSP70 promoterregulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
128
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(133 citation statements)
references
References 38 publications
4
128
0
1
Order By: Relevance
“…Therefore, it is worthwhile to examine whether MDR phenotype could be restored by inhibition of a constitutively active HSF found in MDR cells. In order to answer this question, MDR cells were treated with quercetin, which is known to inhibit heat shock protein synthesis after heat shock in a human colon carcinoma cell line and Hela cells (Hosokawa et al, 1992) and also interfere with the formation of the complex between the HSE and HSF and downregulate the level of HSF1 (Nagai et al, 1995). In this study, quercetin appeared to inhibit dose-dependently the constitutive HSF DNA-binding activity and the sodium arsenite-induced HSF DNA-binding activity in the MDR cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is worthwhile to examine whether MDR phenotype could be restored by inhibition of a constitutively active HSF found in MDR cells. In order to answer this question, MDR cells were treated with quercetin, which is known to inhibit heat shock protein synthesis after heat shock in a human colon carcinoma cell line and Hela cells (Hosokawa et al, 1992) and also interfere with the formation of the complex between the HSE and HSF and downregulate the level of HSF1 (Nagai et al, 1995). In this study, quercetin appeared to inhibit dose-dependently the constitutive HSF DNA-binding activity and the sodium arsenite-induced HSF DNA-binding activity in the MDR cells.…”
Section: Discussionmentioning
confidence: 99%
“…Since FM3A/M and P388/M MDR cells showed a constitutive HSF DNA-binding activity under the non-stressed condition (Kim et al, 1997) and quercetin has been shown to interfere with the formation of the complex between the HSE and HSF, and to downregulate the level of HSF1 (Hosokawa et al, 1992;Nagai et al, 1995). It was examined whether the constitutive HSF activity in MDR cells could be downregulated by quercetin.…”
Section: Effect Of Quercetin On Constitutive and Sodium Arsenite-indumentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 The present study investigated the effects of quercetin on the acceleration of matrix Figure 4. The time course changes of HSP70 and the expression of extracellular matrix genes in articular cartilage after microwave (MW) irradiation.…”
Section: Effects Of Quercetin On Hsp70 Induction and Matrix Gene Exprmentioning
confidence: 99%
“…In brief, 108 astrocytes were exposed to hypoxia (24 h) and reoxygenated (6 h) in either the presence or the absence of quercetin (100 suM) (Hosokawa et al, 1992), followed by labeling with [3H] leucine (100~.rCi/ml) for 30 mm. Cells were homogenized in PBS containing NP-40 (0.5%), EDTA (1 mM), and cycloheximide (100~ug/ ml) using a Dounce homogenizer.…”
Section: Preparation Of Polysomal Fraction and Incorporation Of [3h] mentioning
confidence: 99%